THU0461 Class I and Class II Hdacs Make Distinct Contributions to the Inflammatory Activation of Rheumatoid Arthritis Fibroblast-Like Synoviocytes. (10th June 2014) - Angiolilli, C.; Grabiec, A.M.; Tak, P.P.; Baeten, D.L.; Reedquist, K.A.
Abstract : Background: HDAC inhibitors (HDACi) display anti-inflammatory properties in animal and in vitro models of rheumatoid arthritis (RA), as well as initial safety and efficacy in the treatment of systemic onset juvenile idiopathic arthritis 1, 2 . However, most currently available HDACi display relatively little selectivity for class I (HDAC 1-3, 8) and class II (HDAC 4-7, 9, 10) HDACs. Objectives: The present study aims to better characterize the different contributions of HDAC family members to the inflammatory activation of RA fibroblast-like synoviocytes (FLS). Methods: HDAC mRNA expression in RA FLS was measured by quantitative PCR, and the activity of class I, IIa and IIb HDACs was assessed by enzymatic assays. The effects of pan-specific HDACi and selective HDAC1/2, HDAC3/6 and HDAC8 inhibitors on RA FLS gene expression was analyzed by ELISA and customized qPCR arrays. FLS were either transduced with adenoviral GFP-HDAC5 or transfected with HDAC5 siRNA, and gene expression was analyzed by qPCR array, while chemokine production was measured by ELISA. Analysis of transcription factors was performed using DNA-binding and ELISA-based assays. Results: Class IIa HDAC5 mRNA expression, but not class IIa HDAC activity, is significantly and selectively reduced after RA FLS stimulation with TNFα and IL-1β. The decrease in HDAC5 levels in RA FLS, mimicked by the use of specific siRNA targeting HDAC5, leads to nuclear accumulation of IRF1 transcription factor, concomitant with the increased mRNA and protein expression of a subset of CXCL chemokines. Unlike class IIa HDACs, class I and class IIb HDACs display higher enzymatic activity upon inflammatory stimuli. Impairment of class I HDAC3 and class IIb HDAC6 activity by the use of a selective HDAC3/6 inhibitor significantly reduced by two-fold or more the expression of 80% of 84 IL-1β –inducible genes targeted by pan-specific HDACi in RA FLS. In contrast, inhibitors targeting HDAC1/2 and HDAC8 activity had little effect on gene expression. Conclusions: Our results show that mRNA expression and activity of distinct HDAC members in RA FLS are regulated in a different fashion by inflammatory stimuli. Silencing of class IIa HDAC5 increases CXCL chemokine production, associated with enhanced nuclear accumulation of IRF1, while selective combined inhibition of HDAC3 and HDAC6 suppresses the expression of genes similarly downregulated by pan-specific HDACi. Our results suggest that the design of HDACi targeting specific HDACs can be used to selectively modulate inflammatory gene expression in RA References: Joosten, L. A., F. Leoni, S. Meghji, and P. Mascagni. 2011. Inhibition of HDAC Activity by ITF2357 ameliorates Joint Inflammation and Prevents Cartilage and Bone Destruction in Experimental Arthritis. Mol. Med. 17: 391-396. Vojinovic J, Damjanov N, D'Urzo C, et al. Safety and efficacy of an oral histone deacetylase inhibitor in systemic-onset juvenile idiopathic arthritis. Arthritis Rheum 2011;63:1452–8. Acknowledgements: B.S. Ferguson and T.McKinskey, University of Colorado – Denver, Denver, CO. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4360